Do people with arthritis differ from healthy controls in their internal comparison standards for self-reports of health, fatigue, and pain? - Doerte U. Junghaenel; Stefan Schneider; Arthur A. Stone (SpringerOpen, 2019)
Abstract Objective Patient-reported outcomes are central for the assessment and treatment of people with chronic disease. The primary aim of this study was to determine if people with arthritis differed from healthy individuals in their use of internal comparison standards when answering questions about their health and symptomatology. A secondary aim was to determine if average levels of the patient-reported outcomes were associated with the use of internal comparison standards, regardless of whether a participant had arthritis or no chronic medical condition. Methods People with a self-report diagnosis of any type of arthritis (n = 588) and healthy controls (n = 567) were recruited from an Internet panel and were randomly assigned to rate two of three outcomes: health, fatigue, and pain. After completing their rating, participants were presented with internal comparison standards and indicated which ones, if any, they used for the ratings they provided. The internal comparison standards were: Interpersonal (comparisons with other people); Historical (comparisons with the past); Imaginary comparisons (comparisons with a hypothetical scenario); or that none of the three were used. Results After controlling for group differences in demographic characteristics and outcome levels by including them in the analyses as covariates, people with arthritis were more likely to make Historical comparisons than healthy controls when rating their health. No other group differences in the use of internal comparison standards were found. We further found that the use of internal comparison standards was associated with health and symptom levels, regardless of whether a participant had arthritis or no medical condition. Poorer self-rated health, greater fatigue, and higher pain were associated with a greater likelihood of making a Historical comparison. Furthermore, poorer self-rated health was associated with a greater likelihood of making an Interpersonal comparison, and higher fatigue and pain with a greater likelihood of making an Imaginary comparison. Conclusion People with arthritis differed in their use of Historical comparison standards compared to those with no chronic medical condition for health ratings. In addition, poorer health and more severe symptomatology were associated with the use of internal comparison standards in both groups of participants, people with arthritis and healthy controls.